The impact of integrated TQM and interactivity on customer retention process - Faed, Alireza (Human and Sciences Publication, 2011)
Customer relationship management (CRM) and total quality management (TQM) are two significant tools that have emerged to enhance effectiveness and profitability of business entities. They are concentrated on customer satisfaction. Although TQM is compatible with the customer relationship environment, constructive interactivity also adds harmonious value. Today, companies are challenging each other, not only to win customers but also to gain customers from competitors from a variety of business channels. Companies encountering complaints are exposed to loss of customers and revenue. In response a system to handle the complaints in an effective way is more than desirable. Too commonly, due to the complexity of business processes, companies suffer from lack of interactivity and weak customer loyalty. In this paper, usingTQM and interactivity within the CRM environment, we attempt to increase the level of customer retention. We then provide a secure environment for a myriad of transactions comprising virtual or physical exchanges. This is intended to diminish the level of customer complaints and mitigate threats to the business from complaints received. We benefit from a conceptual framework to identify the problematic areas. We conclude this study with enhancement of customer satisfaction, profitability of the company as well as proper control over customers using a conceptual framework.